Diagnóstico de coronavirus canino en cachorros con gastroenteritis en la ciudad de Machala - Gonzaga Peláez, Raúl Fernando (2008)
The present investigation has more than enough canine Coronavirus he/she was carried out in the you take care of Machala, county of The Gold, during the months of February and March of the 2008, with the following objectives: 1. to diagnose the canine Coronavirus in puppies with gastroenteritis in the city of Machala, 2. to Determine the infection percentage for canine Coronavirus in puppies with gastroenteritis, 3. to Establish a distribution among, age, race, sex, 4. to Establish a geographical distribution of the infection. The number of investigated animals was of 100 those that presented symptoms gastroentericos and they had less than 6 months. For the taking of sample was used the quick test of Parvovirus and canine Coronavirus and the results were written down in the leaf of registrations that contained the patient's origin, it dates, race, sex, age, symptoms, result of the test and the case number. The prevalencia of canine Coronavirus in the city of Machala was of 13% the infection grade it is high considering that it is the first time that is carried out this investigation. In the urban sub population we obtained 4 infection%.